A role for tetracycline selection in recent evolution of agriculture-associated Clostridium difficile PCR ribotype 078 - Dingle, K; Didelot, X; Quan, T; Eyre, D; Stoesser, N; Marwick, C; Coia, J; Brown, D; Buchanan, S; Ijaz, U; Goswami, C; Douce, G; et al. (American Society for Microbiology, 2019)
The increasing clinical importance of human infections (frequently severe) caused by Clostridium difficile PCR-ribotype 078 (RT078) was first reported in 2008. The severity of symptoms (mortality ≤30%) and higher proportion of infections among community and younger patients, raised concerns. Farm animals, especially pigs, have been identified as RT078 reservoirs. We aimed to understand the recent changes in RT078 epidemiology, by investigating a possible role for antimicrobial selection in its recent evolutionary history. Phylogenetic analysis of international RT078 genomes (isolates from 2006-2014, n=400), using time-scaled, recombination-corrected, maximum likelihood phylogenies, revealed several recent clonal expansions. A common ancestor of each expansion had independently acquired a different allele of the tetracycline resistance gene, tetM. Consequently, an unusually high proportion of RT078 genomes were tetM positive (76.5%). Multiple additional tetracycline resistance determinants were also identified (including efflux pump tet40), frequently sharing a high level of nucleotide sequence identity (up to 100%) with sequences found in the pig pathogen, Streptococcus suis and other zoonotic pathogens such as C. jejuni and C. coli. Each RT078 tetM-clonal expansion lacked geographic structure, indicating rapid, recent international spread. Resistance determinants for C. difficile infection-triggering antimicrobials, including fluoroquinolones and clindamycin were comparatively rare in RT078. Tetracyclines are used intensively in agriculture; this selective pressure, plus rapid, international spread via the food-chain may explain the increased RT078 prevalence in humans. Our work indicates that the use of antimicrobials outside the healthcare environment has selected for resistant organisms, and in the case of RT078 contributed to the emergence of a human pathogen.